Personality influences responses to inequity and contrast in chimpanzees. (March 2015) - Brosnan, Sarah F.; Hopper, Lydia M.; Richey, Sean; Freeman, Hani D.; Talbot, Catherine F.; Gosling, Samuel D.; Lambeth, Susan P.; Schapiro, Steven J.
Abstract : Several species besides humans respond negatively to inequity (i.e. receiving a less preferred outcome as compared to a social partner). Among primates, the taxon for which inequity responses have been most comprehensively studied, there are large individual differences in responses that have, thus far, not been well explained by demographic features such as sex, rank and age. Recent evidence shows that individuals' personalities are important in explaining differences in behavioural outcomes in other contexts. Thus, in the current study, we explored whether personality was associated with chimpanzees' responses to both inequity and contrast (i.e. receiving less than anticipated). Chimpanzees were paired with multiple members of their social groups. These pairs alternated trading a token to receive food rewards that either differed from what their partner received (inequity condition) or from what was initially offered (contrast condition) and we compared their responses to a control in which both subjects were offered and received the same reward for trading the token. We predicted that both personality and the quality and length of the pairs' relationship would influence subjects' reactions to unequal outcomes, as measured by their refusal to exchange tokens. The quality of subjects' relationships, based on a weighted average of grooming, contact and proximity, did not correlate with refusals to exchange, whereas pairs that had lived together longer were less likely to refuse in the contrast condition than were pairs that had lived together for less time. Considering personality, some of the dimensions influenced responses to both inequity and contrast similarly, but the more 'social' personality dimensions ('extraversion' and 'agreeableness') were more strongly correlated with sensitivity to inequity. These results highlight the importance of considering individual differences, including personality, when evaluating responses in cognitive and behavioural tests. Highlights: We examined the effects of personality on chimpanzees' responses to inequity and contrast. Extraversion and agreeableness were correlated with sensitivity to inequity. The quality of the pairs' relationship did not explain variation in responses to inequity. Longer-term associates were less likely to refuse in the contrast condition. Personality is important when evaluating subjects' responses in cognitive and behavioural tests.